THE ROLE OF PR EVOLUTION THROUGH AI-POWERED SOCIAL MEDIA MONITORING: STRATEGIES FOR MEASURING CAMPAIGN SUCCESS - Diana Lutfiana; Novi Erlita; Reonaldo Suryanata (Jurnal Visi Komunikasi, 2026)
the advent of social media and the integration of artificial intelligence (AI). This study explores the efficacy of AI-powered social media monitoring tools in evolving PR practices and measuring campaign success. Through a qualitative research approach, semi-structured interviews were conducted with three social media researchers who utilize these tools in their professional roles. The study aims to understand the subjective experiences of these researchers, the capabilities and limitations of AI technologies, and the impact of AI on key PR metrics such as brand awareness, reputation, and crisis management. The findings reveal that AI-powered social media monitoring tools significantly enhance the ability of PR professionals to track and analyze large volumes of social media data in real-time. Participants highlighted the benefits of these tools in identifying trends, tracking engagement, and conducting sentiment analysis. However, the study also identifies several challenges, including difficulties in capturing nuanced human emotions and occasional inaccuracies in sentiment classification. These findings align with existing literature, which emphasizes the transformative potential of AI in PR while acknowledging current technological limitations. The study concludes by identifying best practices for integrating AI-powered social media monitoring into PR strategies and highlighting opportunities for future research. These include improving sentiment analysis algorithms, developing AI tools capable of interpreting complex emotions, and exploring the ethical implications of AI in PR. By providing a nuanced understanding of the role of AI in PR, this research offers valuable insights for practitioners and stakeholders, guiding the effective and responsible use of AI technologies in the field.